What are the immunologically active components of Bacille Calmette‐Guérin in therapy of superficial bladder cancer? - Zlotta, Alexandre R.; Van Vooren, Jean‐Paul; Denis, Olivier; Drowart, Annie; Daffé, Mamadou; Lefèvre, Pascal; Schandene, Liliane; De Cock, Michel; De Bruyn, Jacqueline; Vandenbussche, Paul; Jurion, Fabienne; Palfliet, Kamille; et al. (International journal of cancer, 2000)
The subcomponents of bacille Calmette‐Guérin (BCG) involved in the mechanism of action of intravesical BCG immunotherapy used for prophylaxis of superficial bladder cancer recurrences have been poorly investigated. We purified various BCG subcomponents and analyzed in vitro their ability to enhance a Th1 polarized immune response as well as to increase lymphocyte‐mediated cytotoxicity against bladder tumors. Human peripheral blood mononuclear cells (PBMCs) from healthy purified protein derivative–positive subjects were incubated for 7 days with whole BCG and various fractions (BCG cell wall, plasma membrane, cytosol, purified polysaccharides as glucan or arabinomannan, purified native proteins from BCG culture filtrate, recombinant 22 kDa protein, phosphate transporter PstS‐2 and ‐3 proteins). IFN‐γ, IL‐12, IL‐2, and IL‐6 production by stimulated PBMCs was compared to unstimulated controls and the phenotype of expanded cells analyzed by flow cytometry (FACS analysis). A 51Cr‐release assay monitored the cytotoxicity of amplified effector cells against T24 bladder tumor cells. Live BCG and most of its subcomponents (with the exception of cytosol, PstS‐2 and ‐3) significantly enhanced IFN‐γ and IL‐12 secretion, expanded CD3–CD56+ cells and the non‐MHC‐restricted cytotoxicity against bladder tumor cells compared to unstimulated controls (all P < 0.001, t‐test). IL‐2 receptor blockage resulted in a clear reduction in the cytotoxic activity of stimulated PBMCs. Numerous BCG subcomponents thus provide positive stimuli for Th1 cell differentiation and enhance in vitro, non‐MHC‐restricted cytotoxicity against bladder tumor cells. Our findings provide the basis for the therapeutic use of several of these subfractions in experimental animal models bearing bladder tumors. Int. J. Cancer 87:844–852, 2000. © 2000 Wiley‐Liss, Inc.